Preliminary Stress Corrosion Cracking Modeling Study of a Dissimilar Material Weld of Alloy (Inconel) 182 with Stainless Steel 316 in Pressurized Water Nuclear Reactor - Aly, Omar Fernandes; Neto, Miguel Mattar; de Abreu Mendonça Schvartzman, Mônica Maria (Journal of Technology Innovations in Renewable Energy, 2014)
Dissimilar welds (DW) are normally used in many components junctions in structural project of PWR (Pressurized Water Reactors) in Nuclear Plants. One had been departed of a DW of a nozzle located at a Reactor Pressure Vessel (RPV) of a PWR reactor, that joins the structural vessel material with an A316 stainless steel safe end. This weld is basically done with Inconel/Alloy 182 with a weld buttering of Inconel/Alloy 82. It had been prepared some axial cylindrical specimens retired from the Alloy 182/A316 weld end to be tested in the slow strain rate test machine located at CDTN laboratory. Based in these stress corrosion susceptibility results, it was done a preliminary semi-empiric modeling application to study the failure initiation time evolution of these specimens. The used model is composed by a deterministic part, and a probabilistic part according to the Weibull distribution. It had been constructed a specific Microsoft Excel worksheet to do the model application of input data. The obtained results had been discussed according with literature and also the model application limits.